(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
In the present study, the various variables are illustrated as a result of which the educational environment is getting worse both in educational organizations and in homes. My study also brings in the views of students, teachers and the parents as what kind of strategy should be adopted to raise the educational standards. Also to give schools the regard of Gurukul like our older educational system and will develop the relationship of Eklavaya and Dronaacharya.